1995
DOI: 10.1111/j.1365-2141.1995.tb05582.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonal B‐cell expansions in peripheral blood of HCV‐infected patients

Abstract: Clonal expansions of IgM-producing B cells were investigated in 38 patients with a chronic hepatitis C virus infection. Eight patients were affected with type II mixed cryoglobulinaemia (two of whom also had non-Hodgkin's lymphoma and one had Waldenström's disease), one with type III mixed cryoglobulinaemia, one with Waldenström's disease, and 28 with chronic liver disease. To detect the clonal B-cell expansions we used a RT/PCR procedure in which the CDR3/FW4 regions of the IgM heavy chain mRNAs were amplifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
76
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(83 citation statements)
references
References 14 publications
6
76
0
1
Order By: Relevance
“…The pathogenetic link between HCV and the immune system in inducing both autoimmunity and lymphproliferation is unclear. The persistence of HCV in peripheral blood mononuclear cells, preferentially in B-cells [15], results in chronic stimulation of B-cells, leading to polyclonal and later to monoclonal proliferation of RF (IgMk)-producing cells, which may result eventually in malignant transformation and development of overt lymphoma [16][17][18][19]. The recent identification of CD81 protein as one of the HCV receptor candidates on B-lymphocytes [20] provides a mechanism by which B cells are infected with or activated by HCV and may raise a wide spectrum of interesting issues regarding the pathogenetic link between HCV infection, autoimmunity and lymphoproliferative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenetic link between HCV and the immune system in inducing both autoimmunity and lymphproliferation is unclear. The persistence of HCV in peripheral blood mononuclear cells, preferentially in B-cells [15], results in chronic stimulation of B-cells, leading to polyclonal and later to monoclonal proliferation of RF (IgMk)-producing cells, which may result eventually in malignant transformation and development of overt lymphoma [16][17][18][19]. The recent identification of CD81 protein as one of the HCV receptor candidates on B-lymphocytes [20] provides a mechanism by which B cells are infected with or activated by HCV and may raise a wide spectrum of interesting issues regarding the pathogenetic link between HCV infection, autoimmunity and lymphoproliferative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the presence of abnormal clonal B cell populations in the liver and blood of HCV-infected individuals (5)(6)(7)(8). Clonal B cells from patients with HCV-related B cell lymphoproliferation preferentially use the IgH V H 1-69 and Igk V k 3 gene segments, which can encode RF of the WA idiotype (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…This observation confirms and expands previous descriptions of clonal B-cell population in the blood of HCV-infected persons, as well as clonal B-cell infiltrates in the bone marrow and liver biopsies of patients with HCV infection, associated or not with cryoglobulinemia. [22][23][24][25][26] These infiltrates were shown to remain unmodified during a long follow-up in most cases but can be followed up as overt lymphoma in about 10% of them. The term 'monotypic lymphoproliferative disorder of undetermined significance' 1 has been proposed for these cases.…”
Section: Discussionmentioning
confidence: 99%